The correlation between high sensitivity C-Reactive Protein level and the Extent of Coronary Lesion and Cardiac Systolic Function in Coronary Heart Disease (Medical Journal of Indonesia, 2003)
To determine the mean value of high sensitivity C-Reactive Protein (hs-CRP), association between plasma level of hs-CRP with extent of disease and systolic function. A cross sectional study had been conducted to 106 coronary artery disease patients (90 stable angina pectoris, 11 unstable angina pectoris and 5 acute myocardial infarction). Plasma quantitative level of hs-CRP with cor angiography to determine extent of disease and ejection fraction were measured. The mean of hs-CRP levels in patients with SVD were 5,5 ± 7,6 mg/L, DVD were 6,6 ± 21,7 mg/L and TVD were 5,5 ± 8,0 mg/L and p=0,056, respectively. There were no significant association between hs- CRP levels with extent of disease. Systolic function had negative correlation with levels of hs-CRP (p=0,015, r=-0,235). This study showed that plasma level of hs-CRP cannot reflect the extent of disease, and it had negative correlation with systolic function. (Med J Indones 2003; 12: 201-6)